Behavioral Biases of Individual Investors’ Decision-Making in Emerging Markets: A Mediation Approach - Sharma, Dilli Raj; Adhikari, Madhav; Khatun, Insha (Journal of Emerging Management Studies, 2024)
Purpose – This paper investigates the interplay between behavioral biases, financial risk propensity, and investment decisions among individual investors in Nepal’s emerging capital market. It explores how biases such as overconfidence, loss aversion, herding, experiential, disposition, and familiarity biases influence investment outcomes directly and through financial risk propensity as a mediator. Design/methodology/approach – A structured questionnaire was used to collect data from 327 investors who were active in the Nepal Stock Exchange. The research employed correlation and regression analyses to examine the relationships between behavioral biases, financial risk propensity, and investment decisions. Mediation analysis was conducted to assess the role of financial risk propensity in between behavioral biases and investment decisions. Findings – The results revealed that biases such as loss aversion, herding, and experiential bias have significantly impacted on investment decisions. Financial risk propensity, encompassing return expectations, diversification, and time horizon, mediates these effects. Young and novice investors have dominated the Nepal’s share market, exhibiting heightened susceptibility to behavioral biases and limited portfolio diversification. Implications – The findings emphasize the need for tailored financial literacy programs, regulatory measures promoting diversification, and strategies to mitigate behavioral biases. Policymakers and financial advisors can use these insights to foster more informed and rational investment behavior. Originality/value – This research contributes to the behavioral finance literature by validating the mediating role of financial risk propensity in an emerging market context. It provides empirical insights into investor behavior in Nepal, offering valuable implications for other similar economies.